La familia en el proceso de rehabilitación de las personas internas en la Comunidad Terapéutica “Salvando al Adicto” de la ciudad de Loja - Romero Erazo, Ángela Jackeline (2017)
The primary purpose of this study focused on the need to identify as "the family in the rehabilitation process of the insiders in the therapeutic community''salvando to adicto'' city Loja" acts, seeking preventive strategies to avoid alcohol and relapse of inmates, based on the management and understanding of the drug problem. The characteristics of this study were social research on the method of scientific research, research design was developed in four phases: diagnosis, planning, implementation and evaluation. For this study was taken as informants to 23 internal residents''Salvando Rehabilitation Center to Adicto'' the city and province of Loja, who I were given a structured interview as a tool for gathering information. For the analysis and interpretation of information categorization and triangulation it was applied, and then make the appropriate theorizing. The results allowed us to conclude that the problems presented in the Rehabilitation Centre is `` The limited participation of the family in the rehabilitation process does not allow for an effective recovery of people with alcohol addiction Rehabilitation Center Community `` Saving therapeutic Adicto'' City Loja'', so that the implementation of tools that provide internal and your family need a comprehensive training and the ability to solve their problems with creative responses and adjusted to their 5 reality it is necessary that the family and the internal address this problem generating forms of prevention, which aims to: Improve family relationships for efficient prevention and rehabilitation of these diseases through a participation to generate knowledge, habits and behaviors which are designed to solve the current problems.